Processing of Soybean and Its Derivatives as a Source of Protein in Animal Feed - Marcia, Abigail
Soybeans have high protein content and are suitable as source of protein in animal feed. The processing of soybean is expected to produce protected protein, which can increase its absorption in ruminant’s digestion. One method of protein processing is heat treatment. Protein dispersibility index (PDI) is a measurement of protein solubility which correlates with microbial degradation in ruminants. In this case, a high solubility indicates high ruminal degradation. This study aims to determine the effect of time, temperature, and heating method on the protein quality. The parameter used as a reference for protein quality is the PDI, which represents the ratio between the crude protein soluble supernatant and crude protein in the solution. The parameter of protein quantity was represented by CP (crude protein), which was measured by Kjeldhal method as protein content of the sample. Variations in this study include raw materials (soybean and tofu residue), heating methods (convection oven and extruder), temperatures (60°C and 90 °C) and time (15-90 minutes for convection ovens and 1- 5 minutes for extruder). Heating extrusion for 3 minutes could decrease the PDI at pH 7 to 25% (60°C) compared to protein without treatment (58%). This result suggests that the heated protein may be suitable for ruminants feed. It was found that there was an increase in the crude protein content as the heating duration increased. The product with the highest crude protein content was obtained by extruder at a temperature of 90°C, which had a crude protein content of 46% -wet basis.